31Phosphorus magnetic resonance spectroscopy of the liver for evaluating inflammation and fibrosis in autoimmune hepatitis. (3rd August 2017) - Puustinen, Lauri; Hakkarainen, Antti; Kivisaari, Reetta; Boyd, Sonja; Nieminen, Urpo; Färkkilä, Martti; Lundbom, Nina; Arkkila, Perttu
Abstract: Background: Liver biopsy is the gold standard in evaluating inflammation and fibrosis in autoimmune hepatitis. Aims: In search of non-invasive follow-up tools in autoimmune hepatitis, we evaluated 31 phosphorus magnetic resonance spectroscopy ( 31 P MRS). Methods: Twelve consecutive AIH patients (mean age 42.8 years, 10 women) underwent liver biopsy, routine laboratory liver function tests, which were compared to findings in 31 P MRS and transient elastography (TE). Results: Phosphoenolpuryvate (PEP) correlated with the grade of inflammation ( r  = 0.746, p  = .005) and thromboplastin time ( r  = 0.592, p  = .043). It also differentiated patients with active inflammation from patients without ( t  = 3.781, p  = .009). There was no correlation between PEP and aminotransferase or immunoglobulin G levels. The phosphoethanolamine (PE)/phosphocholine (PC) ratio, PE/glyserophosphoethanolamine (GPE) ratio and PC/[total phosphomonoester (PME) + phosphodiester (PDE)] ratios correlated with immunoglobulin G ( r  = 0.764, p  = .006; r  = 0.618, p  = .043; and r = −0.636, p  = .035, respectively). PME/PDE and PE/GPE correlated with fibrosis ( r  = 0.668, p  = .018 and r  = 0.604, p  = .037). PE/GPE also differentiated F3 from F0-2 patients ( t  = 3.810, p  = .003). Phosphorus metabolites did not correlate with TE results and TE did not correlate with liver histology or laboratory parameters. Conclusions: 31 P MRS seems to detect active inflammation and advanced fibrosis in AIH patients. TE was ineffective in fibrosis quantification.